Aerosolized pH1N1 influenza infection induces less systemic and local immune activation in the lung than combined intrabronchial, nasal and oral exposure in cynomolgus macaques. (25th December 2020) - Mooij, Petra; Mortier, Daniella; Stammes, Marieke; Fagrouch, Zahra; Verschoor, Ernst J.; Bogers, Willy M. J. M.; Koopman, Gerrit
Abstract : Non-human primates form an important animal model for the evaluation of immunogenicity and efficacy of novel 'universal' vaccine candidates against influenza virus. However, in most studies a combination of intra-tracheal or intra-bronchial, oral and nasal virus inoculation is used with a standard virus dose of between 1 and 10 million tissue culture infective doses, which differs from typical modes of virus exposure in humans. This paper studies the systemic and local inflammatory and immune effects of aerosolized versus combined-route exposure to pandemic H1N1 influenza virus. In agreement with a previous study, both combined-route and aerosol exposure resulted in similar levels of virus replication in nose, throat and lung lavages. However, the acute release of pro-inflammatory cytokines and chemokines, acute monocyte activation in peripheral blood as well as increased cytokine production and T-cell proliferation in the lungs were only observed after combined-route infection and not after aerosol exposure. Longitudinal evaluation by computed tomography demonstrated persistence of lung lesions after resolution of the infection and a tendency for more lesions in the lower lung lobes after combined-route exposure versus upper and middle lung lobes after aerosol exposure. Computed tomography scores were observed to correlate with fever. In conclusion, influenza virus infection by aerosol exposure is accompanied by less immune-activation and inflammation in comparison with direct virus installation, despite similar levels of virus replication and development of lesions in the lungs.